A Study of the Accessibility of Ten States' Web Services and their Policies on Web Accessibility for People with Disabilities - David W. Klein; Daniel Kresowik; LeeAnn McCoy (Disability Studies Quarterly, 2005)
Six Web-based services from 10 state websites were assessed for accessibility for people with disabilities. Five states with strong web accessibility policies and five with relatively weak accessibility policies were selected for comparison. Among a variety of measures for accessibility, including "Bobby," strong policy state websites were compared against weak policy state websites. Strong policy states showed a difference in the number of links on pages, their use of JavaScript, and a trend in how they passed Bobby priority 1. However, no other evidence of any apparent effect from strength of policy was found for accessibility on these websites. Overall, states showed similar levels of accessibility to other public websites in other similar studies. Issues and ways to improve state website accessibility are explored.